Elastomery : konstitutivní modelování, identifikace materiálových parametrů a porovnání s experimentem - Poživilová, Alena (Ústav termomechaniky, Dolejškova 5, 182 00 Praha 8, http://www.it.cas.cz/, 2002)
In the contribution the description of large elastic deformations of rubber-like materials is discussed. This theory is verified by experimental evidence.
Keywords: constitutive modelling; hyperelasticity; elastomers